Homeland security education: Managerial versus nonmanagerial market perspectives of an academic program. Issue 4 (18th May 2016) - Doss, Daniel; Henley, Russ; McElreath, David; Lackey, Hilliard; Jones, Don; Gokaraju, Balakrishna; Sumrall, William
ABSTRACT: The authors discuss the findings of a market study that preceded the offering of an academic program in homeland security. The university disseminated a mail survey to gain data for analysis of variance testing of several hypotheses regarding market perceptions of the intended homeland security program offering. Stratification involved segregating responses into categories of managers versus nonmanagers. Four statistically significant findings were observed regarding perceptions of course titles, academic program characteristics, degree types, and degree titles. The outcomes of the study are described within the article, and recommendations regarding the implications of the market study are discussed.